Hubungan Islamic Marketing Ethics dan Customer Satisfaction pada Perbankan Syariah - Fataron, Zuhdan Ady (BISNIS, 2021)
Islamic marketing ethics in Islamic institutions are used to encourage customer satisfaction. The purpose of this study is to examine the relationship between Islamic marketing ethics and customer satisfaction in Islamic banking. The method used in the preparation of this article is a literature review. Based on the discussion of the previous literature, it can be denied that Islamic banking has a stable existence and tends to experience positive growth every year. Islamic banking is one form of business in general that requires a marketing strategy so that sharia marketing ethics becomes the basic concept in marketing. Marketing ethics that prioritizes morality, honesty, and openness represent ethical values that can shape customer preferences. The advantages of Islamic banks in interest-free products with profit and share principles must be packaged in Islamic marketing ethics so as to build customer confidence. Products that are trusted and free from customer complaints that serve customer satisfaction optimally. The formation of customer satisfaction is able to create long-term customer loyalty so that it can maintain the financial performance of Islamic banks.